Solve for y -3(y-3)=-7y+29

Math
-3(y-3)=-7y+29
Simplify -3(y-3).
Tap for more steps…
Apply the distributive property.
-3y-3⋅-3=-7y+29
Multiply -3 by -3.
-3y+9=-7y+29
-3y+9=-7y+29
Move all terms containing y to the left side of the equation.
Tap for more steps…
Add 7y to both sides of the equation.
-3y+9+7y=29
Add -3y and 7y.
4y+9=29
4y+9=29
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 9 from both sides of the equation.
4y=29-9
Subtract 9 from 29.
4y=20
4y=20
Divide each term by 4 and simplify.
Tap for more steps…
Divide each term in 4y=20 by 4.
4y4=204
Cancel the common factor of 4.
Tap for more steps…
Cancel the common factor.
4y4=204
Divide y by 1.
y=204
y=204
Divide 20 by 4.
y=5
y=5
Solve for y -3(y-3)=-7y+29

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top